2016
DOI: 10.1080/02688697.2016.1206185
|View full text |Cite
|
Sign up to set email alerts
|

Short versus long-segment posterior fixation in the treatment of thoracolumbar junction fractures: a comparison of outcomes

Abstract: Our data identified a trend towards better clinical and radiological outcomes in the LSPF, compared to the SSPF group. Although supported by some studies, these findings should be evaluated in future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
1
24
0
2
Order By: Relevance
“…18 Although there was no statistical significance between the 3 different levels of fixation, the superiority of the 2/2 construct on fracture reduction and maintenance of correction can be because of the extra stiffness and strength it provides compared to the other constructs. 12 Tezeren et al compared 2/2 vs. 1/ 1 fixations and found similar results; 2/2 fixations being superior at both reducing and controlling the fracture. The same conclusion was made by Waqar et al in their series looking at long vs. short fixations.…”
Section: Review Of the Literaturementioning
confidence: 91%
See 3 more Smart Citations
“…18 Although there was no statistical significance between the 3 different levels of fixation, the superiority of the 2/2 construct on fracture reduction and maintenance of correction can be because of the extra stiffness and strength it provides compared to the other constructs. 12 Tezeren et al compared 2/2 vs. 1/ 1 fixations and found similar results; 2/2 fixations being superior at both reducing and controlling the fracture. The same conclusion was made by Waqar et al in their series looking at long vs. short fixations.…”
Section: Review Of the Literaturementioning
confidence: 91%
“…The same conclusion was made by Waqar et al in their series looking at long vs. short fixations. 12 On the contrary Sapkas et al found that both long and short fixation reduce the fracture equally well but long fixation control it better in the long term. 19 Park et al compared fixations of 1/1 vs. 2/1 and found no differences in fracture reduction and maintenance of the correction.…”
Section: Review Of the Literaturementioning
confidence: 96%
See 2 more Smart Citations
“…Fractures of the thoracolumbar junction and upper lumbar spine (T12-L2) are common injuries as a result of high-energy trauma with potentially devastating consequences including pain, neurological injury, and loss of function [1]. The main strategy of surgical treatment for thoracolumbar fractures (TLF) has been neurologic decompression, anatomic reduction, stabilization, and fusion [2,3].…”
Section: Introductionmentioning
confidence: 99%